Unified growth theory: Roots of growth and inequality in the wealth of nations - Oded Galor (Rockwool Foundation Berlin (RFBerlin), 2025)
What sparked humanity's leap from stagnation to prosperity? What lies at the core of inequality among nations? Unified Growth Theory explores the evolution of societies over the entire course of human history. It uncovers the universal wheels of change that have governed the journey of humanity, driven the growth process, and shaped inequality across the globe. The theory sheds light on two of the most fundamental mysteries surrounding this journey: (i) The Mystery of Growth-the origins of the dramatic transformation in human prosperity over the past two centuries, in the wake of millennia of near stagnation; and (ii) The Mystery of Inequality-the roots of the vast inequality in the wealth of nations. The theory suggests that forces operating in the distant past are central to the understanding of the uneven development across the globe and the design of effective policies that could promote economic growth and mitigate inequality.
Keywords: I25; J10; O10; 040; Z10; 330; Growth; Inequality; Unified Growth Theory; Human Capital; Demographic Transition; Malthusian epoch